The gap between the need for parental support and support provided during the COVID-19 pandemic: a qualitative study with first-time mothers' experiences - Heléne Appelgren Engström; Marie Golsäter; Maria Harder (BMC, 2024)
Abstract Background Becoming a parent can be challenging. Becoming a parent for the first time during the COVID-19 pandemic might pose additional challenges, as the pandemic has imposed restrictions on society, thus affecting parental support. There were changes in parental support from child health services and preschools available for all children and their parents, so called open preschools, have been closed. This study explored first-time parents' experiences of the parental support they received during the COVID-19 pandemic. Methods A qualitative study involving individual semi-structured interviews with nine first-time mothers who had been on parental leave during the pandemic was conducted. Data were analyzed with inductive content analysis and the results are presented in a main category with three generic categories. Results The main category is entitled, A gap between the needs of parental support and the support provided, and it encompasses three generic categories: The first category, Formal support, refers to support from child health nurses and open preschools. The second category, Lack of formal support, encompasses the lack of person-centred support and lack of parental groups. The third category, Informal support, encompasses support from family, friends, and social media. Conclusions The findings indicate that under the restrictions imposed by the pandemic, first-time mothers expressed the need for person-centred support to both parents which will ensure that all parents get the support they expect and need. The participants also expressed a desire for adapted parental groups that are feasible despite the restrictions to allow them to connect with other parents and build networks.